Naïve Justice in the Ancient Greek Novel - MacQueen, Bruce D. (ETHICS IN PROGRESS, 2016)
This article discusses three trial scenes from three different ancient Greek novels (by Chariton, Achilles Tatius, and Longus), in which naïve justice seems to be deliberately subverted. The titular concept of “naïve justice” is defined here in terms borrowed from Aristotle’s Poetics, where the term “double resolution” is used, disparagingly, of plots in which the good characters are all rewarded and the bad characters all punished. The argument is made that the trial scenes under discussion should raise doubts in the reader’s mind as to which of the parties is truly guilty, and which is truly innocent. This can be seen as a reflection of unexpectedly mature ethical sensibilities on the part of these often-underestimated writers, who seem to have grasped that the “double resolution” may make the reader feel good, but has little to do with the real world.